2007
DOI: 10.1080/10942910701221731
|View full text |Cite
|
Sign up to set email alerts
|

Firmness Properties of Mangoes

Abstract: The purpose of this research was to determine the firmness of mango fruit at different stages of maturity. Immature, mature, and over mature fruit from two Thai mango cultivars (Nam Dokmai and Chok Anan) were subjected to two firmness measuring techniques: a slow compression technique using the Universal Testing Machine and a high-speed impact sensing technique using the low-mass impact tester. The firmness of a mango as determined by the compression test was expressed by the slope of the force-deformation gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Jarimopas and Kitthawee (2007) reported reduced activity of fruit softening enzymes including polygalacturonase, pectin methylesterase, pectatelyase and endo-β-1, 4-glucanase at low temperature. Colour change in mango fruits is attributed to breakdown of chlorophyll as new pigments (mainly carotenoids) are synthesized (Ueda, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Jarimopas and Kitthawee (2007) reported reduced activity of fruit softening enzymes including polygalacturonase, pectin methylesterase, pectatelyase and endo-β-1, 4-glucanase at low temperature. Colour change in mango fruits is attributed to breakdown of chlorophyll as new pigments (mainly carotenoids) are synthesized (Ueda, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Firmness of mango fruit (cv. Nam Dokmai and Chok Anan) has been studied and found to remain relatively unchanged from the immature to the fully mature stages, although firmness rapidly decreased as the fruit ripened (Jarimopas and Kitthawee, 2007). There was a report on quantification of the mechanical characteristics of the textural profile of mango fruit, cv.…”
Section: Introductionmentioning
confidence: 97%
“…Specific weight is also a physical and physiological property that is recognized by horticulturists and post harvest technologists. It has been investigated by researchers to determine the maturity of mango (Jarimopas and Kittawee, 2007), mangosteen (Sornsrivichai et al, 1999) as well as dragon fruit (Wanitchang and Jarimopas, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jarimopas and Kittawee (2007) subjected mango to slow compression as a means of determination of the relationship between firmness and maturity. They found that the slope remained constant from immaturity to maturity but decreased as the fruit became overmature.…”
Section: Introductionmentioning
confidence: 99%